A Literature-based Overview of Current Narratives on the Capacitation of Community Leaders in Addressing the Challenges of Climate Change Mitigation and Adaptation - Shadreck Muchaku (Environmental Science and Sustainable Development)
In most many countries worldwide, community leaders (CLs) are expected to play an important role in mobilising and soliciting contributions from others for the proactive implementation of climate change adaptation strategies. Due to a lack of capacity at the local leadership level, several local-level climate change mitigation and adaptation initiatives have not been effectively actioned with most of them frequently excluding local decision-makers, and key community stakeholders. Basing assessment on what is available in the literature, it is evident that there is urgent need for the scientific community to develop innovative strategies that facilitate the meaningful implementation of informed climate change policies. To successfully address the challenges of climate change, this paper posits that it is necessary for researchers, policy makers and planistrators must endeavour to explore and implement actionable local-level climate change mitigation and adaptation strategies. The take-home message from this paper is that the time to act is now and refrain from doing so until it is too late to do so for tomorrow may never come. The likely implications for the benefits of proactive and effective community leaders are considered against this backdrop and insights from literature-based multi-level governance, participatory learning, action-oriented transformative leadership initiatives that were sourced from the literature.